THE URGENCY OF DIGITAL LITERACY SKILLS FOR EDUCATORS TO FACE GLOBAL CHALLENGES IN SOCIETY 5.0 ERA - Rangga Alif Faresta (Jurnal Kependidikan, 2023)
The development of technology has had a significant impact on various sectors, especially in the field of Education. Where teachers can develop their competencies in the digital field. However, with the advancement of technology, teachers are expected to be able to operate various learning platforms and select and choose the information that is well-received in the era of open information. So in the Society 5.0 era, one of the important skills that teachers must have is digital literacy. The method used in this research is a literature study. The collection and analysis of references through various literature related to digital literacy and the Society 5.0 era. The research results show that digital literacy plays a crucial role in supporting learning activities. Therefore, improving digital literacy competencies is highly needed to face various challenges in the field of education in the Society 5.0 era.